The phytochemical properties of a new citrus hybrid (Citrus hystri x Citrus microcarpa) - Yahya, Abdul Halim; Chong, Gun Hean; Tan, Chin Ping (Science Society of Thailand, 2014)
The Merdeka lime is a new citrus hybrid with strong resistance against pests and disease. This work aims to provide information about the total phenolic content (TPC), total flavonoid (TF) content and antioxidant potential of the leaves, peel and pulp of this new hybrid along with those of its parent plants (Citrus hystrix and C. microcarpa). The TPC and TF contents were determined based on a colorimetric method, while antioxidant levels were determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and the ferric-reducing antioxidant power (FRAP) techniques. The results revealed that Merdeka lime contained the highest TPC (4600±140 µg gallic acid equivalents per gram of dry weight) and DPPH value (4260±30 µg Trolox equivalents per gram of dry weight) in the leaves and the highest TF (16 400±300 µg quercetin equivalents per gram dry weight) and FRAP value (13 430±60 µg ascorbic acid equivalent per gram of dry weight) in the peel. The antioxidant activities of Merdeka lime were similar to the parent plants.